2021
DOI: 10.1093/gerona/glab111
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aerobic or Resistance Exercise, or Both, on Intermuscular and Visceral Fat and Physical and Metabolic Function in Older Adults With Obesity While Dieting

Abstract: Background Obesity exacerbates age-related effects on body composition, physical and metabolic function. Which exercise mode is most effective in mitigating these deleterious changes in dieting obese older adults is unknown. Methods In a randomized controlled trial, we performed a head-to-head comparison of aerobic (AEX), resistance (REX), or combination (COMB) exercise during matched weight loss in 160 obese older adults. Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 50 publications
5
37
2
Order By: Relevance
“…Furthermore, the between-group differences in HbA1c were also eliminated after adjusting data for changes in fat mass, pointing to the importance of improvement in body composition as a potential mediator of improvement in glucometabolic health [8]. These findings are in line with the recent report from the LITOE that 10% calorie restriction-induced weight loss in combination with aerobic and resistance exercise reduced ectopic fat deposition (visceral and intermuscular fat), findings that correlated with improvement in cardiometabolic profile (i.e., insulin sensitivity index) [16 ▪ ]. Visceral and ectopic fat deposition are in fact associated with low-grade inflammation and insulin resistance in humans and animal models [8].…”
Section: Cardiometabolic Profilesupporting
confidence: 79%
See 2 more Smart Citations
“…Furthermore, the between-group differences in HbA1c were also eliminated after adjusting data for changes in fat mass, pointing to the importance of improvement in body composition as a potential mediator of improvement in glucometabolic health [8]. These findings are in line with the recent report from the LITOE that 10% calorie restriction-induced weight loss in combination with aerobic and resistance exercise reduced ectopic fat deposition (visceral and intermuscular fat), findings that correlated with improvement in cardiometabolic profile (i.e., insulin sensitivity index) [16 ▪ ]. Visceral and ectopic fat deposition are in fact associated with low-grade inflammation and insulin resistance in humans and animal models [8].…”
Section: Cardiometabolic Profilesupporting
confidence: 79%
“…This evidence emphasizes the importance of prescribing calorie restriction in combination with both resistance and aerobic exercise among older adults with obesity [14,15,16 ▪ ,17]. Calorie restriction is in fact necessary to achieve a significant reduction in fat mass content, while exercise is crucial to improve frailty outcomes and prevent the calorie restriction-induced reduction in muscle and bone mass.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we demonstrated that the most important modifiable factor in the development of sarcopenia in elderly men was engaging in RT at least two times per week. Importance of RT is recently being revitalized, as it has been proposed that while aerobic exercise may attenuate the loss of skeletal muscle during energy restriction in obese adults, a single mode of aerobic exercise alone does not promote muscle hypertrophy to the same extent as RT 31–35 . Along the same line, while there was an increasing trend in the onset of sarcopenia according to a decrease in the physical activity level, this association was modest and did not independently contribute to the development of sarcopenia in men.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, decreased muscle CSA and increased fat content in the lumbar paravertebral muscles have been strongly related to lower back pain in adult men and women (Kjaer et al, 2007; Parkkola et al, 1993; Shahidi et al, 2017). Considering the higher fat content in untrained males across multiple muscle groups in this study, it may be suggested that therapeutic interventions should target whole‐body resistance and/or endurance exercise to reduce skeletal muscle fat fraction and, thus, improve skeletal muscle insulin sensitivity, decrease low back pain, and increase muscle CSA (Parkkola et al, 1993; Schumann et al, 2022; Waters et al, 2022).…”
Section: Discussionmentioning
confidence: 99%